Kinetics study on non-isothermal thermochemical liquefaction of corncobs in ethanol-water solution: Effect of ethanol concentration - Sembodo Bregas Siswahjono Tatag; Sulistyo Hary; Sediawan Wahyudi Budi; Fahrurrozi Mohammad (MATEC Web of Conferences, 2018)
Corncobs are potentially processed into bio-oil through thermochemical liquefaction processes. It is difficult to construct kinetics models based on the compounds involved in the reaction. It would be made four kinetic models based on four reaction products, i.e., solids, bio-oil, gas and volatile products. The purposes of the study were to seek kinetics model of thermochemical liquefaction of corncobs in ethanol-water solution and to study the effect of ethanol concentration. The experiment of liquefaction processes of corncobs in ethanol-water solution using sodium carbonate catalyst was performed in the 150 ml autoclave equipped with a magnetic stirrer in the temperature up to 280°C. Four kinetic models were applied to predict the yield of four reaction product lumps. The calculation results were compared to the experimental data. Compared to the others, model 4 was the most realistic and closely matching to the experimental data. In model 4 the reaction mechanism was assumed that biomass (corncobs) first decomposed into bio-oil, followed by decomposition of bio-oil into volatile products reversibly and, finally, volatile products decomposed into gaseous products. The yield of bio-oil increased from 42.05% to 54.93% by increasing to ethanol concentration of 0% to 40%.